China's Role in the New Stage of Russia's Development of Its Eastern Regions. Issue 10 (3rd October 2017) - Dze, S.
Abstract : Russia faces the urgent task of solving the economic and social problems of the underdeveloped regions of Siberia and the Far East. To this end, an important role is played by neighboring Asian countries, which are a major source of investment. Thus, Russia must strengthen its ties with Asia-Pacific countries to socially and economically develop Siberia and the Far East. Of these countries, China is Russia's largest strategic partner in the region.